Retinitis pigmentosa mutations of SNRNP200 enhance cryptic splice-site recognition - Cvačková, Zuzana; Matějů, Daniel; Staněk, David (Human mutation, 2014)
Mutations in SNRP200 gene cause autosomal-dominant retinal disorder retinitis pigmentosa (RP). The protein product of SNRNP200 is BRR2, a DExD/H box RNA helicase crucial for pre-mRNA splicing. In this study, we prepared p.S1087L and p.R1090L mutations of human BRR2 using bacterial artificial chromosome recombineering and stably expressed them in human cell culture. Mutations in BRR2 did not compromise snRNP assembly and both mutants were incorporated into the spliceosome just as the wild-type (wt) protein. Surprisingly, cells expressing RP mutants exhibited increased splicing efficiency of the LDHA gene. Next, we found that depletion of endogenous BRR2 enhanced usage of a β-globin cryptic splice site while splicing at the correct splice site was inhibited. Proper splicing of optimal and cryptic splice sites was restored in cells expressing BRR2-wt but not in cells expressing RP mutants. Taken together, our data suggest that BRR2 is an important factor in 5'-splice-site recognition and that the RP-linked mutations c.3260C>T (p.S1087L) and c.3269G>T (p.R1090L) affect this BRR2 function.
Keywords: reportérové geny; RNA Splice Sites; RNA-helikasy; Ribonucleoproteins, Small Nuclear; Genes, Reporter; alternativní sestřih; Retinitis Pigmentosa; klonování DNA; lidé; HeLa Cells; RNA Precursors; Cloning, Molecular; Mutation; ribonukleoproteiny malé jaderné; beta-Globins; mutace; místa sestřihu RNA; Humans; HeLa buňky; beta-globiny; prekurzory RNA; Spliceosomes; Alternative Splicing; RNA Helicases; spliceozomy; retinopathia pigmentosa